The Effect of Debt Policy, Dividend Policy, Investment Decisions and Corporate Size on Corporate Value - Dewi, Ni Luh Putu Sandrya; Novitasari, Ni Luh Gde (AIBPM Publisher, 2022)
Business development in the era of globalization requires all types and sectors of businesses to compete for survival. A company must implement a strategy that can improve its performance to achieve its goals. A company's value deals with the price a potential buyer would pay when the company is sold. This recent paper examines the impacts of debt policy, dividend policy, investment decisions, and corporate size on the values of IDX-listed manufacturing companies of 2018-2020. We purposively selected 69 manufacturing companies and conducted 207 observations. Research data were analyzed by a multiple linear regression test. The results suggest that debt policy, investment decisions, and company size has a partial effect on firm value. Also, dividend policy has no partial effect on company value.Â Keywords: Company Size, Debt Policy, Dividend Policy, Firm Value, Investment Decision.